Spontaneous tension pneumocephalus and pneumoventricle in ecchordosis physaliphora: case report of a rare presentation and review of the literature. (2nd September 2020) - Ghimire, Prajwal; Shapey, Jonathan; Bodi, Istvan; Connor, Steve; Thomas, Nicholas; Barkas, Konstantinos
Abstract: We describe the case of a 65-year-old lady who presented with mutism and a right hemiparesis. Imaging showed a severe spontaneous tension pneumocephalus. The cause was diagnosed as Ecchordosis physaliphora (EP). EP is a rare cystic congenital hamartomatous benign notochordal tumor (BNCT) arising from an ectopic notochordal remnant. To the authors' knowledge, this is the first case of EP to be described in the literature which presented with a life-threatening but treatable condition of severe tension pneumocephalus.